The Effect of Mixed Liquor Administration on The Johnsen’s Score and The Number of Sertoli Cells and Leydig Cells on The Wistar Strain White Rats (Rattus norvegicus) - Aqidah Khariri1 , Anny Setijo Rahaju2,4, Arifa Mustika3 (Indian Journal of Forensic Medicine & Toxicology, 2021)
To analyze the effect of mixed liquor administration on the Johnsen’s score and the number of Sertoli cellsand Leydig cells on the Wistar strain white rats (Rattus norvegicus). A total of 28 rats were divided into 4groups: C, P1, P2, and P3. Rats were given mixed liquor with different dose, namely P1 (1 ml), P2 (2 ml),and P3 (4 ml) each day for 14 days, then compared to C group which was given 4 ml of distilled water usingan oral gavage. Mixed liquor consists of 20% ethanol and 4% methanol. The histopathological features wereevaluated by the Johnsen’s score, the number of Sertoli cells, and Leydig cells in cross-sectional preparationof rat testicular tissue with 400× magnification. Datas were analyzed using the Kruskal-Wallis test and OneWay ANOVA test with a confidence level of p <0.05. The P3 group had the lowest Johnsen’s score and thenumber of Sertoli cells, 6.442±0.293 and 5.942±0.674, respectively. A significant decrease in increased doseoccurred in the Sertoli cell count but not in the Johnsen’s score. Group P2 had the lowest number of Leydigcells, 6.421±0.360. The administration of mixed liquor caused a decrease in Johnsen’s score and the numberof Sertoli cells and Leydig cells on the Wistar strain white rat (Rattus norvegicus).